Prestasi akademik dan perilaku prososial pada Mahasiswa - Walidatuts Tsalitsah; Eben Ezer Nainggolan; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine student academic achievement in terms of prosocial behavior, through a comparative approach. The subjects of this study were 155 students of the Class of 2019. The data collection method used student GPA data and a prosocial scale. The results showed that the Chi-square value was 3.842 at a significance level of 0.814 (p>0.05), this means that there is no difference in student prosocial behavior in terms of academic achievement. It can be said that the hypothesis that there is a difference in the value of student academic achievement in terms of prosocial behavior cannot be proven. The results of this study prove that the prosocial behavior of students cannot be used as a benchmark for high and low academic achievement. In general, these results also show that subjects who have a GPA range between 2.9 – 4.00 have a tendency to prosocial behavior that is classified as low. For this reason, it is recommended that students improve prosocial behavior that is better and more useful through social activities as activities that support the improvement of student academic achievement. Keywords: Prosocial Behavior, Academic Achievement, Psychology Students